The Conservative Avant-Garde - Richard Schechner (Revista Brasileira de Estudos da Presença, 2012)
This article discusses the so-called artistic avant-garde in the twenty-first century, particularly in regard to theatre and performance art; in other words, this text brings into question the current state of those forms of expression. It discusses the concepts of avant-garde, nicheguard and conservatism in order to deal with the conservative status of the avant-garde in the group of artistic expressions mentioned above, that actually merely repeats previous achievements rather than proposing new forms of transgression and disruption of the established order, including the one that running the art system. The article is based on the idea that the avant-garde exists in three realms simultaneously – as a living tradition, as a brand, and as the echo or ghost of the provocation it once was.